The “Discouraged Worker Effect” in public works programs: Evidence from the MGNREGA in India - Narayanan, Sudha; Das, Upasak; Liu, Yanyan; Barrett, Christopher B. (International Food Policy Research Institute, 2017)
This study investigates the consequences of poor implementation in public workfare programs, focusing on the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) in India. Using nationally representative data, we test empirically for a discouraged worker effect arising from either of two mechanisms: administrative rationing of jobs among those who seek work and delays in wage payments. We find strong evidence at the household and district levels that administrative rationing discourages subsequent demand for work. Delayed wage payments seem to matter significantly during rainfall shocks. We find further that rationing is strongly associated with indicators of implementation ability such as staff capacity. Politics appears to play only a limited role. The findings suggest that assessments of the relevance of public programs over their lifecycle need to factor in implementation quality.